New realizations of CMOS current controlled conveyors with variable current gain and negative input resistance - Al-Shahrani, S.M. (2003)
In this paper two new second-generation current controlled current-conveyors (CCCIIs)-based circuits are proposed. The proposed circuits are variable gain CCCII and CCCII with negative resistance. The design of these circuits is based on a simple CMOS CCCII that has high bandwidth with -3 dB cutoff frequency of 580 MHz. With no signal mirroring used in these configurations, lower harmonic distortion can be achieved. HSPICE simulation results for the proposed circuits are included.